Investment Security in the Development of the Digital Economy - Kalinin, Oleksandr (Dr. Viktor Koval, 2024)
Introduction. Investment security in the development of the digital economy forms the basis for enhancing the digital competitiveness of European countries, ensuring the development of a pan-European data space, strengthening cybersecurity, stimulating the activity of underdeveloped economic sectors, and driving the digital transformation of public healthcare services.  Aim and tasks. The study aims to determine the strategic directions and challenges of enhancing investor support to establish favourable circumstances for the growth of the digital economy in European countries. Results. The advantages of the digital economy as a basis for further human development are identified. According to the analysis of the dynamics of the digital skills indicator, a trend of increasing individual digital skills among people in EU countries with four and five out of five indicator components was observed in 2023 compared to 2021 (an increase ranging from 0.57 to 1.64 percentage points). The leaders in the increase in Internet usage frequency are Romania, Belgium, and Montenegro, with increases of 19.98%, 18.29%, and 17.31%, respectively. The benefits of using digital technologies to enhance business competitiveness and the need to promote digital investment in regions with low levels of digitalisation, which consequently have low investment attractiveness, were identified. This will help counteract the imbalance of digital resources and data exchange, and form the potential for developing competitive digital advantages for European countries’ economies. Conclusions. Obstacles to digitalisation in European countries include an aging population, which contributes to a low level of skilled labour availability and disparities in the adoption of digital technologies. There is a need for continuous monitoring of the implementation of digital transitions in European countries. Digitalisation serves as the main driver of technological innovations and services, productivity growth in economic sectors, and reduced efforts in data analysis and decision-making. Investment security in the digital economy should promote the acceleration of digital transitions in regions with low-capacity levels. The rationality of investment decisions can expedite the development of digital infrastructure as the primary potential for the growth of less-efficient industries on the path to sustainability.